Strategic Learning Management Training during the Covid-19 Pandemic at SMKN 3 Depok - Susan Febriantina; Farah Cantika Azalia; Ponco Dewi Karyaningsih; Roni Faslah; Herlitah Herlitah (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
Schools from all grades from elementary to secondary levels in have recently adopted the so-called remote learning, whether online or offline. The relatively unfamiliar learning conditions triggered some panic, not only among students but also teachers and parents alike. This sudden change also caused a similar shock to the students at SMKN 3 Depok. Consequently, the students experienced decreased enthusiasm and motivation, and many teachers were affected in how they should meet the learning objectives. The strategic learning management training during pandemic for students is a solution to boost the students’ motivation and help organize their learning more strategically. The training method is conducted in material presentation, discussion, question and answer, and experience sharing sessions to 255 students of class X SMKN 3 Depok City. The outcome shows how this activity has reignited the students’ learning enthusiasm and motivation.